2008
DOI: 10.1115/1.2903422
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of the Individual Muscles of the Shoulder to Glenohumeral Joint Stability During Abduction

Abstract: The aim of this study was to determine the relative contributions of the deltoid and rotator cuff muscles to glenohumeral joint stability during arm abduction. A three-dimensional model of the upper limb was used to calculate the muscle and joint-contact forces at the shoulder for abduction in the scapular plane. The joints of the shoulder girdle-sternoclavicular joint, acromioclavicular joint, and glenohumeral joint-were each represented as an ideal three degree-of-freedom ball-and-socket joint. The articulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
82
2
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 120 publications
(97 citation statements)
references
References 33 publications
9
82
2
4
Order By: Relevance
“…The middle deltoid force, for example, was half as big as in our model (van der Helm 1994). Conversely, our results showed different force patterns for the rotator cuff and deltoid muscles compared with the study of Yanagawa et al (2008): infraspinatus and supraspinatus showed almost constant forces during the movement while our stress-based model predicted a maximum at 708 of abduction. Another study calculated muscle forces for glenohumeral abduction up to 808 glenohumeral elevation (Favre et al 2012).…”
Section: Discussioncontrasting
confidence: 85%
“…The middle deltoid force, for example, was half as big as in our model (van der Helm 1994). Conversely, our results showed different force patterns for the rotator cuff and deltoid muscles compared with the study of Yanagawa et al (2008): infraspinatus and supraspinatus showed almost constant forces during the movement while our stress-based model predicted a maximum at 708 of abduction. Another study calculated muscle forces for glenohumeral abduction up to 808 glenohumeral elevation (Favre et al 2012).…”
Section: Discussioncontrasting
confidence: 85%
“…More recently, the Newcastle model was used to evaluate the shoulder biomechanics in several activities of daily living and provided similar results as the Dutch model [8]. Another similar model predicted glenohumeral reaction force of about 70% of the BW during quasi-static abduction in the scapular plane [9]. Other optimization models have been developed for posture control or ergonomics analyses [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Coordinated synchronous activity of shoulder girdle muscles is required to limit translation of the humeral head on the shallow glenoid fossa [Bey et al, 2008;Poppen et al, 1978]. Rotator cuff muscle activity plays a fundamental role in maintaining glenohumeral joint (GHJ) stability [Burkhart, 1991;Inman et al, 1996;Yanagawa et al, 2008], 'stiffening' the GHJ to establish a stable fulcrum [David et al, 2000].…”
Section: Introductionmentioning
confidence: 99%